Fracture mapping of lineaments and recognizing their tectonic significance using SPOT-5 satellite data: A case study from the Bajestan area, Lut Block, east of Iran. (October 2017) - Ahmadirouhani, Reyhaneh; Rahimi, Behnam; Karimpour, Mohammad Hassan; Malekzadeh Shafaroudi, Azadeh; Afshar Najafi, Sadegh; Pour, Amin Beiranvand
Abstract: Syste'm Pour l'Observation de la Terre (SPOT) remote sensing satellite data have useful characteristics for lineament extraction and enhancement related to the tectonic evaluation of a region. In this study, lineament features in the Bajestan area associated with the tectonic significance of the Lut Block (LB), east Iran were mapped and characterized using SPOT-5 satellite data. The structure of the Bajestan area is affected by the activity of deep strike-slip faults in the boundary of the LB. Structural elements such as faults and major joints were extracted, mapped, and analyzed by the implementation of high-Pass and standard kernels (Threshold and Sobel) filters to bands 1, 2 and 3 of SPOT-5 Level 2 A scene product of the Bajestan area. Lineament map was produced by assigning resultant filter images to red-green-blue (RGB) colour combinations of three main directions such as N-S, E-W and NE-SW. Results derived from image processing technique and statistical assessment indicate that two main orientations, including NW-SE with N-110 azimuth and NE-SW with N-40 azimuth, were dominated in the Bajestan area. The NW-SE trend has a high frequency in the study area. Based on the results of remote sensing lineament analysis and fieldwork, two dextral and sinistral strike-slip components were identified as main fault trends in the Bajestan region. Two dextral faults have acted as the cause of shear in the south and north of the Bajestan granitoid mass. Furthermore, the results indicate that the most of the lineaments in this area are extensional fractures corresponding to both the dykes emplacement and hydrothermal alteration zones. The application of SPOT-5 satellite data for structural analysis in a study region has great capability to provide very useful information of a vast area with low cost and time-consuming. Highlights: Lineament features in the Bajestan area, the Lut Block, eastern Iran are mapped using SPOT-5 data. Main fault trends and lineaments are identified in the Bajestan region. The application of SPOT-5 satellite data for structural analysis is very useful.